Cardiovascular Risk Factors in Middle-Aged Lithuanian Men: A Comparative Study of an Apparently Resistant Hypertension Group - Vaida Šileikienė; Vilma Dženkevičiūtė; Alma Čypienė; Martynas Bublys; Roma Puronaitė; Jolita Badarienė; Aleksandras Laucevičius; Eglė Butkevičiūtė; Egidija Rinkūnienė (Biomedicines)
Background/Objectives: Hypertension (HTN) is a significant risk factor for cardiovascular disease (CVD), and a subset of patients exhibits apparently resistant hypertension (aRHTN), where blood pressure remains inadequately controlled despite treatment. This study aims to assess the prevalence of cardiovascular risk factors in middle-aged Lithuanian men with HTN and aRHTN, as well as to evaluate the effectiveness of hypertension management in these groups. Methods: Data from 52,012 men participating in the Lithuanian High Cardiovascular Risk Programme (LitHiR) between 2009 and 2019 were analysed. Participants were categorised into two groups: treated hypertension (HTN) and apparent resistant hypertension (aRHTN). Despite treatment, the aRHTN group included those who failed to achieve their target blood pressure. The prevalence of cardiovascular risk factors (dyslipidaemia, diabetes, metabolic syndrome, obesity, physical inactivity, and an unbalanced diet) was compared between the groups. Results: The overall prevalence of HTN was 47%, with 9.9% of treated hypertensive men having aRHTN. Dyslipidemia was both groups’ most prevalent risk factor (94.1% in HTN vs. 95.5% in aRHTN, p < 0.001). Men with aRHTN exhibited higher rates of diabetes (25.9% vs. 18.5%, p < 0.001), metabolic syndrome (75.3% vs. 66.3%, p < 0.001), and left ventricular hypertrophy (59.4% vs. 43.1%, p < 0.001). Treatment success was significantly lower in the aRHTN group (7.57% vs. 28.4%, p < 0.001). Conclusions: Hypertension affects almost half of the studied population, with 10% of treated hypertensives exhibiting aRHTN. The aRHTN group had a higher number of additional cardiovascular risk factors and lower treatment success rates. Improved management of cardiovascular risk factors is crucial, especially in the aRHTN population, to reduce the burden of CVD.